JOGO ELETRÔNICO PARA ENSINO DA 1º LEI DE OHM E DO CONCEITO DE POTÊNCIA ELÉTRICA ENVOLVENDO PRÁTICAS EXPERIMENTAIS - Zapotoczny, Ivo Antônio (2022)
This work presents an electronic game developed from the Arduino prototyping platform, with the aim of contributing to the teaching of Ohm's first law and concepts involving electrical power, making use of a gamified environment, where simplified laboratory practices and simulations aimed at solving problem situations, both fictitious and everyday, designed to serve teachers who do not have adequate physical space for laboratory practices, or the possibility of carrying out experimental activities that require more than one class. In addition to seeking to highlight the possible ability of the device to motivate students to want to learn, as well as identifying signs of significant learning, using the pre- and posttest method, to carry out a quantitative analysis and a qualitative analysis to show a differentiation progressive and integrative reconciliation, which are indicators of meaningful learning.